2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00378
|View full text |Cite
|
Sign up to set email alerts
|

Relation Networks for Object Detection

Abstract: Although it is well believed for years that modeling relations between objects would help object recognition, there has not been evidence that the idea is working in the deep learning era. All state-of-the-art object detection systems still rely on recognizing object instances individually, without exploiting their relations during learning.This work proposes an object relation module. It processes a set of objects simultaneously through interaction between their appearance feature and geometry, thus allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
854
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,316 publications
(855 citation statements)
references
References 61 publications
0
854
0
1
Order By: Relevance
“…Object detection has attracted a great deal of attention in recent years [4,13,14,16,19,20,27,28,30,38,39,43,47,48,56]. One popular direction for recent object detection is proposal-based object detectors (a.k.a.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Object detection has attracted a great deal of attention in recent years [4,13,14,16,19,20,27,28,30,38,39,43,47,48,56]. One popular direction for recent object detection is proposal-based object detectors (a.k.a.…”
Section: Related Workmentioning
confidence: 99%
“…Previous works have shown that object detectors can benefit from context [2,7,19,33] and should be noiserobust [31,48]. Our self-supervised proposal learning module uses a proposal location loss and a contrastive loss to learn context-aware and noise-robust proposal features respectively.…”
Section: Self-supervised Proposal Learningmentioning
confidence: 99%
“…In the literature, there has been strong evidences on the use of object relation to support various vision tasks, e.g., recognition [48], object detection [17], cross-domain detection [2], and image captioning [52]. One representative work that employs object relation is [17] for object detection in images. The basic idea is to measure relation features of one object as the weighted sum of appearance features from other objects in the image and the weights reflect object dependency in terms of both appearance and geometry information.…”
Section: Introductionmentioning
confidence: 99%
“…, one can see even for the Nodule, which has a small lesion area, the network with the bottom‐up and top‐down structure performs better, this mainly because the large receptive field of view can extract more contextual information about disease. The contextual information around a lesion will be conducive to the diagnosis of disease, because if a lesion occurs in one location, nearby tissue will also change. In addition, we realized that the two structures that with and without bottom‐up and top‐down structures have almost the same performance for Fibrosis, in theory, the network with a large receptive field of view should have a significant improvement.…”
Section: Discussionmentioning
confidence: 99%